Renalase inhibition defends against acute and chronic β cell stress by regulating cell metabolism - Tara L. MacDonald; Birgitta Ryback; Jéssica Aparecida da Silva Pereira; Siying Wei; Bryhan Mendez; Erica P. Cai; Yuki Ishikawa; Meagan Arbeau; Gordon Weir; Susan Bonner-Weir; Stephan Kissler; Peng Yi (Molecular Metabolism)
Objective: Renalase (Rnls) is annotated as an oxidase enzyme. It has been implicated in Type 1 diabetes (T1D) risk via genome-wide association studies (GWAS). We previously discovered through CRISPR screening and validation experiments that Rnls inhibition prevents or delays T1D in multiple mouse models of diabetes in vivo, and protects pancreatic β cells against autoimmune killing, ER and oxidative stress in vitro. The molecular biochemistry and functions of Rnls are largely uncharted. Here we studied the mechanisms of Rnls inhibition that underlie β cell protection during diabetogenic stress. Methods: Akita mice were treated with oral Pargyline (PG) in vivo to bind and inhibit Rnls, and pancreas or islets were harvested for β cell mass and β cell function analyses. Genetic and pharmacological tools were used to inhibit Rnls in β cell lines. RNA sequencing, metabolomics and metabolic function experiments were conducted in vitro in NIT-1 mouse β cell lines and human stem cell-derived β cells. Results: In vivo, PG improved glycemia and mildly preserved β cell mass and function in females. Genetic strategies to mutate (Rnlsmut) or knockout (Rnls KO) Rnls induced a robust metabolic shift towards glycolysis in both mouse and human β cell lines, in vitro. Stress protection was abolished when glycolysis was blocked with 2-deoxyglucose (2-DG). Pharmacological Rnls inhibition with PG did not strongly mimic these newly identified metabolic mechanisms. Conclusions: Our work illustrates a role for Rnls in regulating cell metabolism. We show that inhibiting Rnls protects against chronic stress in vivo, and shields against acute stress in β cell lines in vitro by rewiring cell metabolism towards glycolysis.